Ramucirumab and durvalumab for previously treated, advanced non–small-cell lung cancer, gastric/gastro-oesophageal junction adenocarcinoma, or hepatocellular carcinoma: An open-label, phase Ia/b study (JVDJ). (September 2020) - Bang, Yung-Jue; Golan, Talia; Dahan, Laetitia; Fu, Siqing; Moreno, Victor; Park, Keunchil; Geva, Ravit; De Braud, Filippo; Wainberg, Zev A.; Reck, Martin; Goff, Laura; Laing, Naomi; et al.
Abstract: Background: Emerging evidence supports combining immune checkpoint inhibitors (ICIs) with conventional or targeted therapies to enhance ICI antitumour activity and broaden the spectrum of patients who respond to ICIs. Here, we present the safety and preliminary efficacy of ramucirumab, an anti-VEGFR2 IgG1, plus durvalumab, an anti–PD-L1 IgG1, in previously treated patients with advanced non–small-cell lung cancer (NSCLC), gastric/gastro-oesophageal junction adenocarcinoma (gastric/GEJ), or hepatocellular carcinoma (HCC). Patients and methods: A 25-centre, phase Ia/b single-arm, non-randomised, multi-cohort study was undertaken in patients with advanced/metastatic disease, Eastern Cooperative Oncology Group performance status, 0–1, progression on prior therapy, no prior ramucirumab or immunotherapy and any PD-L1 status. Patients received ramucirumab (10 mg/kg) plus durvalumab (1125 mg) intravenously Q3W (NSCLC), or ramucirumab (8 mg/kg) plus durvalumab (750 mg) Q2W (gastric/GEJ, HCC). Results: Phase Ia treatment was found safe for phase Ib expansion; final enrolment was NSCLC (n = 28), gastric/GEJ (n = 29), HCC (n = 28). Grade ≥3 treatment–related adverse events occurred in 32.1%, 37.9% and 42.9% of patients, respectively. The most common were fatigue (35.7%), hypertension (34.5%) and diarrhoea (28.6%), respectively. Two patients died owing to an adverse event; one was treatment-related (hepatitis acute, HCC cohort). Objective response rate was 11% for NSCLC and HCC and 21% for gastric/GEJ. Median progression-free survival and overall survival were, respectively, 2.7 and 11 months in NSCLC; 2.6 and 12.4 months in gastric/GEJ; 4.4 and 10.7 months in HCC, with more prolonged survival in patients with high PD-L1 expression. Conclusion: Ramucirumab/durvalumab exhibited manageable safety. The combination showed antitumour activity in all cohorts, particularly in patients with high PD-L1 expression. Highlights: The clinical efficacy of immune checkpoint inhibitor monotherapy appears limited to a subset of patients. The combination of ramucirumab with durvalumab was well tolerated by patients. Blockade of both VEGFR2 and PD-L1 pathways can potentially increase clinical benefit. Dual blockade might expand the subset of patients with non–small-cell lung cancer, gastric/gastro-oesophageal junction adenocarcinoma and hepatocellular carcinoma responding to an immune checkpoint inhibitor.